2018
DOI: 10.1111/trf.15013
|View full text |Cite
|
Sign up to set email alerts
|

Time interval between antibody investigations among patients who demonstrate serial red cell antibody formation

Abstract: BACKGROUND Current national standards for pretransfusion testing do not address the frequency or optimal time interval to repeat antibody identification testing for patients in whom antibodies have been previously detected. STUDY DESIGN AND METHODS A retrospective review was performed of patients with existing red blood cell (RBC) antibodies who subsequently developed new antibody specificities. Data were drawn from a single institution where the antibody investigation was repeated if the screen suggested a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 10 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…A recent study showed it may be possible to extend antibody identification beyond 3 days as long as there is no change in the antibody screen or a positive crossmatch 22 . In cases where patients have warm autoantibodies and are receiving phenotyped RBCs for transfusion, it may also be possible to extend workups beyond 3–14 days or longer; specifics would need to be determined by each individual TS/BB and tailored for their patient population 23 …”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed it may be possible to extend antibody identification beyond 3 days as long as there is no change in the antibody screen or a positive crossmatch 22 . In cases where patients have warm autoantibodies and are receiving phenotyped RBCs for transfusion, it may also be possible to extend workups beyond 3–14 days or longer; specifics would need to be determined by each individual TS/BB and tailored for their patient population 23 …”
Section: Resultsmentioning
confidence: 99%
“…In previously alloimmunized individuals, the rate of additional antibody formation increases by 2–20 fold. 1 As an attempt to reduce the incidence of RCA, many centers have implemented prospective extended antigen matched PRC transfusions for multi-transfused patients to minimize the risk of RCA. However, the patients can still develop alloantibodies despite Rh-K matched PRC transfusions, as seen in our index case.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of red cell alloimmunization (RCA) is proportional to the number of transfusions. 1 It occurs mainly due to antigen mismatched packed red cell (PRC) transfusions. A minor proportion of cases is attributed to platelets.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, practices vary in different laboratories. 7,8 It is possible a new antibody may be masked if it reacts with the same screening cells as the known antibody but would have been identified if an ABID had been repeated more frequently. As a crossmatch is not a full-proof method, the patient may also then be transfused with units positive for the respective antigen for the missed antibody.…”
mentioning
confidence: 99%
“…While there are publications addressing the potential frequency of missing antibodies when an ABID is not performed every 3 days, they do not provide details on the clinical consequences of missing antibodies and then transfusing units positive for the respective antigens. 7,8 In this context, we sought to determine if our policy of repeating an ABID every 30 days puts patients at significant risk of aHTRs. To provide information related to potential financial effects, data are also included on the cost of repeat ABIDs.…”
mentioning
confidence: 99%